The Saint of Beersheba - Weingrod, Alex (State University of New York Press, 1990)
Jones traces the St. Nicholas legend from its origins in 4th c. Asia Minor through the Middle Ages to its form in 19th c. New York. A reprint of the 1978 original. Investigates the yearly pilgrimage and celebration at the grave of Rabbi Chayam Chouri (1885-1957), a Tunisian Jewish leader who emigrated to Israel in 1955. Weingrod (anthropology, Ben Gurion University, Beersheba, Israel) pursues historical and anthropological questions of sainthood and devotion in modern Israel. Includes photographs. Paper edition (unseen), $10.95. Annotation copyrighted by Book News, Inc., Portland, OR.
Keywords: Chouri, Chayim, -- -1957.; Chouri, Chayim, -- -1957; Jewish pilgrims and pilgrimages -- Israel -- Beersheba.; Zaddikim -- Africa, North -- Biography.; Zaddikim -- Israel -- Beersheba -- Biography.; Beersheba (Israel) -- Religious life and customs.; Saints juifs -- Afrique du Nord -- Biographies.; Saints juifs -- Israël -- Beersheba -- Biographies.; SOCIAL SCIENCE -- Sociology of Religion.; Jewish pilgrims and pilgrimages; Zaddikim; North Africa; Israel -- Beersheba; Biographies; Biographies.